Learning Needs and Barriers to Accessing Sexual Health Services among Adolescents: A Descriptive Qualitative Study - Srijaiwong, Sitanan; Tantalanukul, Seubtrakul (Journal of Thailand Nursing and Midwifery Council, 2025)
Introduction Adolescent sexual health during the transitional phase from childhood to adulthood represents a critical issue requiring heightened attention particularly in an era marked by rapid information exchange and prevailing societal attitudes that remain resistant to comprehensive sex education. Despite ongoing efforts to promote sexual education and expand youth-friendly health services, access remains constrained by a constellation of factors at the personal, family, school, and health services system levels. These challenges are especially pronounced within the cultural context of Northern Thailand, where traditional values continue to shape perceptions and practices surrounding sexuality. Understanding adolescents’ learning needs and the barriers they face in accessing services through the perspectives of multiple stakeholders is essential for designing interventions appropriately. Objectives This study aimed to 1) describe perceptions regarding the learning needs, barriers, and access to sexual health services among adolescents of reproductive age within Health Region 2, 2) explore perceptions of sexual communication with children and adolescents, as perceived by students, teachers, and parents, and 3) study perceptions and proposed strategies for developing youth-friendly sexual health services, based on perceptions of students and public health personnel. Design This study employs a descriptive qualitative research design, grounded in the constructivist/ interpretivist paradigms, to explore the perceptions and perspectives of multiple stakeholders regarding adolescent sexual health. The researchers applies a health service development framework including 3 components: 1) learning needs, 2) barriers to service access, and 3) stakeholder experiences and perceptions. Additionally, the study employs the concepts of positive sexual health approach and youth-friendly services as theoretical foundations. Methodology This study was conducted within Health Region 2, including five provinces: Phitsanulok, Phetchabun, Tak, Sukhothai, and Uttaradit, between September 2022 and June 2023. Informants were selected through purposive sampling and snowball sampling techniques, resulting in a total of 100 informants. These included 50 students in late primary and early secondary education (aged 9–15 years), 20 parents, 15 teachers, and 15 public health personnel. Instruments for data collection comprised semi-structured interview guides, focus group discussion protocols, non-participatory observation forms, and personal information recording sheets. The data were gathered through 50 in-depth interviews, 8 focus group discussions, and non-participatory observations conducted at 15 sites. Content analysis was conducted following the approach outlined by Elo and Kyngäs, utilizing NVivo 12 software. Trustworthiness was ensured through member checking, triangulation across data sources, researchers, and methods, and researcher reflexivity. Results The data analysis revealed three major themes aligned with the study’s objectives. First, Learning Needs: Students’ learning needs regarding sexual health were categorized into five sub-themes: 1) physical changes and self-care, 2) relationship and communication skills, 3) sexual protection and safety, 4) safe technology and online media use, and 5) sexual diversity and acceptance. Among students who had previously accessed health services, four areas for service improvement were identified: enhancing service delivery processes, developing modern educational media, expanding online platforms, and providing training for service providers. Barriers to accessing information and services consisted of four main categories: attitude and belief-related barriers (3 subcategories), barriers to accessing accurate information (4 subcategories), health system-related barriers (5 subcategories), and family and school-related barriers (3 subcategories). Second, Perceptions of Sexual Communication: Students perceived that parents and teachers lacked confidence in discussing sexual topics. Teachers reported feeling unprepared and lacking communication skills, while parents expressed concerns that such discussions might stimulate curiosity and acknowledged their own limited access to up-to-date knowledge. Third, Perceptions of Current Services and Recommendations for Youth-Friendly Development: Students perceived existing services as unfriendly and judgmental. Public health personnel reported constraints in time and specialized skills. Recommendations for developing youth-friendly services, as identified across stakeholder groups, included four key areas: 1) improving service environments and processes, 2) enhancing personnel capacity, 3) integrating innovation and technology, and 4) fostering networks and collaborative partnerships. Recommendation Based on the findings, five key recommendations are proposed: 1) Develop an integrated sex education curriculum that incorporates content on evaluating online information and understanding sexual diversity, 2) Establish concrete youth-friendly sexual health services, including dedicated youth clinics, digital counseling applications, and flexible service hours, 3) Create cross-sectoral coordination mechanisms, such as district-level youth sexual health committees and digital referral systems, 4) Enhance parental capacity for sexual communication through tiered communication training programs and peer support groups, and 5) Foster sustainable community engagement by establishing community learning centers and networks of local leaders. This research contributes new knowledge on the diverse and emerging needs of adolescents in the digital era and serves as a foundational resource for policy development and practice that genuinely responds to the lived realities of the target population.